2007
DOI: 10.1002/prca.200700321
|View full text |Cite
|
Sign up to set email alerts
|

Neuroproteomics and its applications in research on nicotine and other drugs of abuse

Abstract: The rapidly growing field of neuroproteomics is able to track changes in protein expression and protein modifications underlying various physiological conditions, including the neural diseases related to drug addiction. Thus, it presents great promise in characterizing protein function, biochemical pathways, and networks to understand the mechanisms underlying drug dependence. In this article, we first provide an overview of proteomics technologies and bioinformatics tools available to analyze proteomics data.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 210 publications
1
5
0
Order By: Relevance
“…Moreover, brain imaging studies in human alcoholics showed a marked reduction in whole brain glucose metabolism and modified brain resource allocation [46], [47]. Neurons adjust their intra- and extra-cellular environment in the presence of alcohol, and a disturbance of energy-generation pathways with related mitochondrial dysfunction could have profound consequences, including generation of reactive oxygen-nitrogen species [45]. Our results provide further support for the role of energy-related changes in two different alcoholic stages.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Moreover, brain imaging studies in human alcoholics showed a marked reduction in whole brain glucose metabolism and modified brain resource allocation [46], [47]. Neurons adjust their intra- and extra-cellular environment in the presence of alcohol, and a disturbance of energy-generation pathways with related mitochondrial dysfunction could have profound consequences, including generation of reactive oxygen-nitrogen species [45]. Our results provide further support for the role of energy-related changes in two different alcoholic stages.…”
Section: Discussionsupporting
confidence: 63%
“…Several proteins identified from the studies above and our current work are involved in basal energy metabolism (e.g., creatine kinase, enolase, malate dehydrogenase, phosphoglycerate mutase 1, pyruvate kinase) [29][31]. Proteins involved in energy metabolism are regulated by many drugs of abuse as shown by neuroproteomic approaches [45]. Moreover, brain imaging studies in human alcoholics showed a marked reduction in whole brain glucose metabolism and modified brain resource allocation [46], [47].…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…This response has been attributed to the nicotine in tobacco smoke 8 . In the drug dependence field, proteomics has been proposed to identify protein patterns that underlie psychological and neurological mechanisms 9 . A study demonstrated rapid effects of stress-induced HPA activation in rats, following only a 15-minute physical stressor 10 .…”
Section: Introductionmentioning
confidence: 99%